Paparan Bahan Kimia Di Tempat Kerja Dan Dampaknya Terhadap Kesehatan Reproduksi - Dealita Khairani Daulay; Dhea Amanda Putri (STIKES Columbia Asia Medan, 2024)
Reproductive health refers to a state of overall well-being that encompasses physical, mental, and social aspects related to reproductive organs, functions, and processes. It plays a crucial role in determining an individual’s fertility, making it essential for individuals to access accurate and reliable information about reproductive health. Occupational diseases are illnesses that are specifically caused or strongly associated with one’s occupation, typically involving a single recognized causative agent (ILO). This research employs the Systematic Literature Review (SLR) method. Data was collected by reviewing articles related to similar studies. A total of 8 national journal articles were selected and used in this research, sourced from the Google Scholar database through the Publish or Perish application.